E-017 Differences in circle of willis geometry between cerebral aneurysm patients and controls. (22nd July 2018) - Kappel, A; Swartwout, E; Lieber, B; Woo, H; Fiorella, D; Sadasivan, C
Abstract : Introduction: Current evidence suggests that hemodynamic factors are associated with the formation and rupture of cerebral aneurysms. 1 As hemodynamics are strongly affected by geometry, objective parameters have also been developed to characterize the three-dimensional vascular geometry obtained from patient scans. 2 Our goal is to evaluate whether such geometric parameters are different between aneurysm patients and controls. Methods: Head and neck CTA acquisitions from 7 aneurysm patients and 10 age and gender matched controls were retrospectively and anonymously analyzed under IRB approval. All aneurysms had ruptured; there were four anterior-communicating (AComm), two posterior-communicating, and one carotid-terminus aneurysm. Mimics software (Materialise, Belgium) was used to segment the vasculature. When available, non-contrast CT scans of the head were linearly co-registered to CT angiograms using Advanced Normalization Tools 3 and used to subtract the cranium and cervical spine for improved segmentation. The average cross-sectional area of the anterior (ACA) and posterior (PCA) cerebral arteries were obtained using VMTK software 4 ; bifurcation angles at the AComm segment were also measured. These three variables were statistically compared (t-test) between the aneurysm and control groups. Results: Both the ACA (p=0.045) and PCA (p=0.025) cross-sectional areas were statistically higher in the aneurysm group as compared to controls (figure 1). AComm bifurcation angles were also greater in aneurysm patients, but not significantly (p=0.55). Conclusions: Previous autopsy studies have suggested an association of ACA asymmetry to the prevalence of ACom aneurysms. 5, 6 Variations in bifurcation and carotid siphon angles have been associated with aneurysms. 7, 8 Our preliminary results are in-line with these studies. A large sample size study is necessary in order to derive any diagnostically relevant associations between Circle of Willis morphology and the etiology of aneurysms. References: Can, Du. Neurosurgery 2016;78:5102. Piccinelli, et al. IEEE Trans Med Imaging 2009;28:11413. Avants, et al. Front Neuroinform 2014;28:444. Antiga, et al. Med Biol Eng Comput 2008;46:10975. Kayembe, et al. Stroke 1984;15:8466. Stehbens. Arch Pathol 1963;75:457. Bor, et al. Neurology 2008;70:7008. Silva Neto ÂR, et al. Arq Neuropsiquiatr 2012;70:917. Disclosures: A. Kappel: None. E. Swartwout: None. B. Lieber: 4; C; Vascular Simulations. H. Woo: 4; C; Vascular Simulations. 6; C; Cerenovus JnJ. D. Fiorella: 1; C; Penumbra, Microvention, Medtronic. 2; C; Penumbra, Microvention, Medtronic. 4; C; Vascular Simulations. 6; C; Cerenovus JnJ. C. Sadasivan: 4; C; Vascular Simulations.